PENGARUH PENAMBAHAN EKSTRAK KULIT PISANG KEPOK (Musa paradisiaca) TERHADAP KECERAHAN WARNA IKAN MASKOKI (Carassius auratus) - Alifia Yumanda Putri; Siti Komariyah; Suri Purnama Febri (Universitas Mataram, 2026)
Goldfish is a fish commodity whose demand continues to increase every year by ornamental fish lovers because of its beautiful color. However, the color fading of goldfish causes the market price of goldfish to decline. This research aims to analyze the effect of adding kepok banana peel extract (Musa paradisiaca) on the brightness of goldfish (Carassius auratus). The method used in this research was a Completely Randomized Design (CRD) with 4 treatments and 3 replications. Where P1 (Without the addition of Kepok banana peel extract), P2 (Kepok banana peel extract 10 ml/kg feed), P3 (Kepok banana peel extract 20 ml/kg feed), and P4 (Kepok banana peel extract 30 ml/kg feed). The results of the research on the level of fish color brightness were obtained in the P3 treatment with a dose of 20 ml/kg feed and the best absolute weight growth was in P4 with a weight increase of 0.84 g, the best absolute length growth was obtained in P4 with a result of 0.99 cm, and the growth rate the best daily was at P4 with a growth rate of 0.69%. The results of the highest feed conversion ratio were found in P4, namely 21.60. Meanwhile, the best survival was found in P1 and P3 with a percentage of 100%.